IMPROVING TEACHING AND LEARNING USING STUDENT APPRAISALS: A CASE STUDY OF A TERTIARY INSTITUTE - Lord, Rigieta (IJRDO- Journal of Educational Research, 2017)
Feedback is being used in education to improve teaching and learning. Through feedback,students are able to gauge their performance and teachers are also able to retrieveinformation to be used to design assessment and make adjustments for improvement.There are various types of feedback that are being discussed in this project, these includedescriptive, evaluative, motivational and effective. These forms of feedback havedifferent purposes which can be summarized to make improvement in the teaching andlearning process. Feedback is being used in the education system to achieve learninggoals and to inform students if they are on the right track or not. There are various waysin which feedback may be done to ensure that it is effective, the following must beconsidered, timely, clear and specific, user friendly to name a few. This project arguesthat student appraisal may be used to improve teaching and learning in a tertiaryinstitution. This project also focuses on the use of student feedback to provide feedbackto the Teaching and Learning Development Unit to design student activities as well asprofessional development session solely to bring about quality assurance. Both studentsand teachers in the tertiary institution have been used as participants of this project.